Towards a circular built environment: An integral design tool for circular building components. Issue 4 (18th October 2020) - van Stijn, Anne; Gruis, Vincent
Abstract : Purpose: The transition to a circular economy in the built environment is key to achieving a resource-effective society. The built environment can be made more circular by applying circular building components. The purpose of this paper is to present a design tool that can support industry in developing circular building components. Design/methodology/approach: The tool was developed and tested in five steps. In Step 1, the authors analysed existing circular design frameworks to identify gaps and develop requirements for the design tool (Step 2). In Step 3, the authors derived circular design parameters and options from existing frameworks. In Step 4, the authors combined and specified these to develop the "circular building components generator" (CBC-generator). In Step 5, the CBC-generator was applied in the development of an exemplary component: the circular kitchen and tested in a student workshop. Findings: The CBC-generator is a three-tiered design tool, consisting of a technical, industrial and business model generator. These generators are "parameter based"; they consist of a parameter-option matrix and design canvasses. Different variants for circular components can be synthesised by filling the canvasses through systematically "mixing and matching" design options. Research limitations/implications: The developed tool does not yet support establishing causal links between "parameter-options" and identification of the most circular design variant. Practical implications: The CBC-generator provides an important step to support the building industry in developing and implementing circular building components in the built environment. Originality/value: Whilst existing tools and frameworks are not comprehensive, nor specifically developed for designing circular building components, the CBC-generator successfully supports the integral design of circular building components. First, it provides all the design parameters which should be considered; second, it provides extensive design options per parameter; and third, it supports systematic synthesis of design options to a cohesive and comprehensive circular design.